State-of-the art CAPEX data for water electrolysers, and their impact on renewable hydrogen price settings. (15th February 2019) - Proost, Joris
Abstract: Within the framework of the Hydrogen Implementing Agreement (HIA) of the International Energy Agency (IEA), a new Task 38 was started early 2016, entitled "Power-to-Hydrogen and Hydrogen-to-X: System Analysis of techno-economic, legal and regulatory conditions". Within this framework, a specific task force was set-up for the compilation of state-of-the-art technical and economical data on large-scale water electrolyser systems, both based on PEM and alkaline technology. The objectives set forward have been twofold. Firstly, to offer policy makers and industry with comprehensive trends and guidelines for further electrolyser cost reduction (CAPEX, in Euro/kW) into the MW-scale. Secondly, to provide objective technological & economic arguments for converging towards a realistic electrolytic (and hence renewable) H2 market price (in Euro/kg). This should help water electrolysis to become competitive with SMR technology for (local) H2 production, and hence to start making H2 a competitive fuel. Highlights: For alkaline, a CAPEX of 750 €/kW is realistic today for a single stack 2 MW system. For PEM, such CAPEX comes within reach for a 5 MW multi-stack system. A CAPEX around 400 €/kW is projected for alkaline systems upon scaling to 100 MW. An electrolytic H2 cost around 3 €/kg is realistic by 2020, comparable to SMR H2 .